Oxygen isotope geochemistry of the Granite Harbour Intrusives, Wilson Terrane, Northern Victoria Land, Antarctica - Dallai L; Ghezzo C; Turi B; Vesica PL (Mineralogy and Petrology, 2002)
The oxygen and strontium isotope compositions of the Cambro-Ordovician granitoids cropping out in the Wilson Terrane (Granite Harbour Intrusives-GHI) constrain the petrological evolution of the magmatism in Antarctica, related to the Ross Orogeny. The measured delta(18)O(WR) values of these intrusives define three different compositional groups: the metaluminous rocks (MAG), with delta(18)O(WR) ranging from 6.9 (olivine gabbro) to 11.4parts per thousand (monzogranite); the unaltered peraluminous granites (PAG), having delta(18)O(WR) values ranging from 10.6 to 13.2parts per thousand, and the foliated peraluminous leucogranites (SKG), characterised by delta(18)O(WR) values above 14parts per thousand. The analysis of equilibrium mineral assemblages indicates that the high delta(18)O(WR) values are magmatic and unaffected by low-temperature processes. A few peraluminous granites sampled in the vicinity of Cenozoic intrusions show anomalously low delta(18)O(WR), due to meteoric-hydrothermal alteration. The isotopic data indicate that the coeval and spatially related metaluminous mafic and felsic intrusives forming the GHI were not comagmatic: the mafic and intermediate rocks were likely derived from lower crustal contamination of a pristine basaltic magma; their delta(18)O(WR) values were also increased during emplacement, due to the interaction with the adjacent O-18-rich hydrous felsic magmas (mixing). Oxygen isotope data indicate that the crustal sources producing the Granite Harbour intrusives were not homogeneous: the felsic metaluminous intrusives were produced by partial melting of fertile rock with possible igneous origin, whereas partial melting of a metapelitic source rock is claimed for the genesis of the peraluminous granites.